Intertextuality: On the use of the Bible in mystical texts - Waaijman, Kees (HTS teologiese studies, 2010)
This article discussed the use of the Bible in mystical texts by focusing on intertextuality as a literary approach which analyses the intersection of texts. It investigated how mystical texts, as phenotexts, relate to the Bible as archetext: firstly, the intertextual relations affect the surface of the text in a mono-causal way and secondly, they govern the production of meaning reciprocally. The article also discussed forms of intersection (quotations, collage, allusions and reproduction) before it analysed the three intertextual strategies producing meaning: participation, detachment and change or rearrangement. Finally, six functions and dimensions of meaning were delineated in the intertextual dynamic between the Bible and the mystical texts. In these the Bible serves as an authoritative framework for argumentation, as a guide and blueprint of the mystical way, as a vocabulary of mystical experience, as an initiation into the divine infinity, as the place of mystical transformation in love and as the articulation of transformation in glory.